Genetic manipulation of betta fish - Palmiotti, Alec; Lichak, Madison R.; Shih, Pei-Yin; Kwon, Young Mi; Bendesky, Andres (Frontiers in Genome Editing, 2023)
Betta splendens, also known as Siamese fighting fish or 'betta', is a freshwater fish species renowned for its astonishing morphological diversity and extreme aggressive behavior. Despite recent advances in our understanding of the genetics and neurobiology of betta, the lack of tools to manipulate their genome has hindered progress at functional and mechanistic levels. In this study, we outline the use of three genetic manipulation technologies, which we have optimized for use in betta: CRISPR/Cas9mediated knockout, CRISPR/Cas9-mediated knockin, and Tol2-mediated transgenesis. We knocked out three genes: alkal2l, bco1l, and mitfa, and analyzed their effects on viability and pigmentation. Furthermore, we knocked in a fluorescent protein into the mitfa locus, a proof-of-principle experiment of this powerful technology in betta. Finally, we used Tol2-mediated transgenesis to create fish with ubiquitous expression of GFP, and then developed a bicistronic plasmid with heartspecific expression of a red fluorescent protein to serve as a visible marker of successful transgenesis. Our work highlights the potential for the genetic manipulation of betta, providing valuable resources for the effective use of genetic tools in this animal model.